Effect of Thymol Incorporation on Antibacterial Activity of the Locally Prepared Zinc Oxide-Guaiacol Root Canal Sealer: An in Vitro Study - Fatin Salim Mohammed; Sawsan H. AL-jubori (University of Mosul, College of Dentistry, 2021)
Aims: This study aims to prepare a new formula by thymol crystals incorporation into locally prepared zinc oxide-guaiacol root canal sealer and evaluating the antibacterial activity and comparing the results with zinc oxide eugenol-based root canal sealer. Materials and Methods: The addition of thymol crystals at three different concentrations (2%, 5%, and 10%) to improve the antibacterial activity of zinc oxide-guaiacol endodontic sealer was done: 40 Petri plates of Enterococcus agar media were used, each plate with five wells. Petri plates divided into four groups incubation intervals (1, 2, 3, and 7 days) for each type, using agar diffusion test (ADT) with 0.5 McFarland turbidity standards and statistically analyzed using descriptive statistics, a one-way ANOVA test, and Duncan's Multiple Range Test. Results: The thymol incorporated zinc oxide-guaiacol sealer groups at studied concentrations (2%, 5%, and 10% ) produced bacterial growth inhibition zones persisted at all incubation time intervals at (1, 2, 3, and 7 days) and high significantly at p≤0.01 than that of zinc oxide eugenol based sealer. There is a significant reduction at p≤0.01 in antibacterial efficacy in all incorporation groups at 7 days incubation period, 5% thymol incorporation group with significant largest bacterial growth inhibition zones for all incubation periods. Conclusions: This study concluded that the pre-pared zinc oxide - guaiacol sealer formulas with three studied thymol crystals concentrations having better antibacterial efficacy than that of zinc oxide eugenol root canal sealer, 5% thymol incorporation formula is the best in antibacterial activity than others.